BUSINESS ACTIVITIES IN RUSSIA - Khodzhamuratova Gulbakhar Yuldashevna (International Journal of Innovations in Engineering Research and Technology, 2022)
This article analyzes the concepts of «business operations» and «the right to business operations» in the context of the constitutional law to business operations and the other economic activities not prohibited by law.